2017
DOI: 10.21010/ajtcam.v14i3.30
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Dental Students’ Attitude Regarding Oriental Medicine/Complementary and Alternative Medicine: Comparison Between Two Japanese Dental Schools

Abstract: Background: The present study aimed to examine the impact of "curricula for undergraduate education in oriental medicine (OM)/complementary and alternative medicine (CAM)" on student awareness of OM. A questionnaire survey was conducted involving the Nagasaki University School of Dentistry (NUSD), a university that implements education in OM as part of its undergraduate curriculum, and Tokyo Dental College (TDC), which does not teach OM. Materials and methods:The third-and fifth-year students of both NUSD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
1
12
1
1
Order By: Relevance
“…According to Clarke et al ( 7) more than 30% of adults in the USA used some sort of complementary health approach in 2012; furthermore, Kemppainen et al found that 25.9% of the general population in Europe used some sort of CAM methods during a 12-month period (8). Most research on the knowledge, attitude, and the use of CAM among medical and health studies students has been conducted in Asia, Africa, and the USA (3)(4)(5)(9)(10)(11)(12). The results of these studies showed that the use of herbal medicine/supplements (9)(10)(11), meditation/Yoga/relaxation/imagery, massage (10), spiritualty and prayer (4, 10) have been found to be very popular.…”
Section: Clinical Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…According to Clarke et al ( 7) more than 30% of adults in the USA used some sort of complementary health approach in 2012; furthermore, Kemppainen et al found that 25.9% of the general population in Europe used some sort of CAM methods during a 12-month period (8). Most research on the knowledge, attitude, and the use of CAM among medical and health studies students has been conducted in Asia, Africa, and the USA (3)(4)(5)(9)(10)(11)(12). The results of these studies showed that the use of herbal medicine/supplements (9)(10)(11), meditation/Yoga/relaxation/imagery, massage (10), spiritualty and prayer (4, 10) have been found to be very popular.…”
Section: Clinical Sciencementioning
confidence: 99%
“…(3) reported that homeopathy was mostly used by pharmacy students. Kampo (Japanese traditional medicine) was most practised among Japanese dental students (12). The most common sources of information on CAM among many students are the Internet (3,10,11), the media (TV, journals) (4, 9, 10, 11), books (3,4,9,10) along with faculty (9), family and friends (3,5,9,11).…”
Section: Clinical Sciencementioning
confidence: 99%
“…However, TM came before modern medicine and was used to treat a variety of medical conditions [ 1 ]. According to the World Health Organisation, 80% of the world’s people depended on TM (herbal) for their primary healthcare needs as these plant extracts were readily accessible, affordable and culturally appropriate [ 4 ]. Also, the economic benefits could be achieved through the development of indigenous medicines and the use of herbal medicines to treat various diseases [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, TM came before modern medicine and was used to treat a variety of medical conditions (1). According to the World Health Organisation, 80% of the world's people depended on TM (herbal) for their primary healthcare needs as these plant extracts were readily accessible, affordable and culturally appropriate (4). Also, the economic bene ts could be achieved through the development of indigenous medicines and the use of herbal medicines to treat various diseases (5).…”
Section: Introductionmentioning
confidence: 99%